Penerapan Face Recognition dengan Algoritma Viola Jones dalam Sistem Presensi Kehadiran Siswa Berdasarkan Titik Lokasi Berbasis Website - Akbar Syarif Pratama Putra; Afu Ichsan Pradana; Anindhiasti Ayu Kusuma Asri; Elia Hari Prasetya (Universitas Islam Raden Rahmat, Malang, 2024)
The Viola-Jones calculation is a commonly used facial recognition calculation. Significant innovation in the form of human facial recognition systems serves as an important security and control tool, and has a variety of other applications. This fits the test's aim of highlighting the usefulness of Viola-Jones calculations in facial recognition, especially in the context of understanding student identity at SMA Negeri 2 Surakarta. This exploration aims to grow the student participation framework at SMA Negeri 2 Surakarta by utilizing facial recognition technology with Viola Jones calculations. remember the focus area. The participation framework creates a plan to improve the adequacy and productivity of supervision of student participation. One is not completely satisfied with the suitability of the registered facial images within the framework of the data set. The digital application used by this facial recognition program is Laravel 11 which is supported on the Windows 11 work system. This test uses 200 images of 20 individuals with different appearances. The cycle achievement rate of facial recognition is approximately 90%. Several elements influence location progress, including lighting, face distance, and face position.